Mechatronic design of an automated storage system located inside a confined space (2014)
It is here presented the mechatronic design of an system with automatic storing and picking of small products. The design concept presents the system as a four degrees-of-freedom robot capable of storing objects at different heights. The novelty of the design lies in the space optimization using stacked trays for storing the desired objetcs. Other key components of the system are a device for entry and exit of products, and a robotic arm for manipulating objects. A typical application of such a system is the storage of products inside safe-deposit boxes is presented. © 2014 IEEE.